1950-1996 yılları arası dini-ilmi muhtevalı periyodiklerde Kelam ile ilgili makaleler bibliyografyası - Yaralıoğlu, Ahmet (My University, 1999)
Söz konusu tarihler arasında yayımlanan 64 tane dergi taranarak Kelâm ilmiyle ilgili makaleler tespit edilmiştir. Bu makaleler teze kelam ilminin sistematik konu başlıklarına göre kronolojik olarak sıralanmıştır. Ayrıca bu araştırmada tez konusuyla benzer bazı örnek çalışmalara da yer verilmiştir. Fikir vermesi bakımından, Türkiye'de dini dergiler üzerine adını taşıyan bir araştırma da yapılmıştır. Taranan dergilerin adları ve kısa tanıtımları da tez de yer almıştır. Tez, bir giriş ve yedi alt başlıktan oluşmaktadır.

TITLE OF THE THESIS:Bibliography Of Articles About Scriptures In Religious-Scientific Periodicals Published Between 1950 And 1996. After searching 64 periodicals in the mentioned years, articles about Scripures science were established. These articles were arranged chronogically according to the titles of Scriptures Science. Furthermore, some studies about similar subject were also discussed in this research. In order to give an idea a research of religious periodicals in Turkey was done into. The name of searched periodicals and their definitions were involved in the thesis. The thesis consists of an Introduction part and seven subtitles.
Keywords: Din; İSLAM; İslam Dini; Tefsir ve tefsir ilmi